Expression of an Anti-Transferrin Receptor Antibody scFV Fragment in Escherichia coli Using A L-Rhamnose-Based Tightly Regulated Promoter System - Andriani, Dian; Handayani, Ira; Kusharyoto, Wien (Annales Bogorienses, 2012)
Transferrin receptor (TfR) levels are elevated in various types of cancer cells and correlate with the aggressive or proliferative ability of tumor cells. Therefore, TfR levels are considered useful as a prognostic tumor marker, and TfR is a potential target for drug delivery in therapy of malignant cells. In such kind of targeted delivery system, antibody fragments are frequently used as targeting moiety. Here, we report the generation of an anti-TfR single-chain antibody variable (scFv). The cDNA encoding the variable heavy and light chain domains of the scFv antibody fragment was derived from the anti-TfR monoclonal antibody LUCA31. The gene encoding the anti-TfR scFv fragment was codon optimized for expression in Escherichia coli, subsequently synthesized, and cloned into the pJExpress-804 Rhamex vector. The expression vector utilizes the E. coli rhaB promoter and corresponding regulatory genes, and is tightly regulated by the presence of L-L-rhamnose, it is also tightly regulated in the absence of L-L-rhamnose by the addition of D-glucose The His6-tagged anti-TfR scFv fragment was expressed in E. coli NiCo21 and purified by means of immobilized metal chelate affinity chromatography on TALON™ matrix. In SDS-PAGE, a single band corresponding to a molecular mass of approximately 30 kDa was observed which corresponded to the predicted molecular mass based on the amino acid sequence.